2002
DOI: 10.1590/s1517-83822002000400011
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties of the cellulase-free xylanase from Thermomyces lanuginosus IOC-4145

Abstract: In recent years, xylanases have expanded their use in many processing industries, such as pulp and paper, food and textile. Thermomyces lanuginosus IOC-4145 was able to produce a very high level of cellulase-free xylanase in shaken cultures using corncob as substrate (500 U/mL). An optimization of the medium composition in submerged fermentation was carried out aiming at a low cost medium composition for enzyme production. Statistical experiment design was employed for this purpose, pointing out corncob as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…To this end, enhanced activity displayed by the xylanase from T. lanuginosus 195 may also be attributed to the increased solubility of oat spelt xylan. A similar preference to oat spelt xylan was also documented by Damaso et al [35] for a xylanase produced by T. lanuginosus.…”
Section: Discussionsupporting
confidence: 81%
“…To this end, enhanced activity displayed by the xylanase from T. lanuginosus 195 may also be attributed to the increased solubility of oat spelt xylan. A similar preference to oat spelt xylan was also documented by Damaso et al [35] for a xylanase produced by T. lanuginosus.…”
Section: Discussionsupporting
confidence: 81%
“…1) in the present study showed a value 3 times greater (15 U/mL) for the endophytic strain of Aspergillus (strain 15). Damaso et al (2002) obtained a xylanase activity of 500 U/mL with Thermomyces lanuginosus IOC-4145 on corn cobs by semi-solid fermentation after 96 h of production. Xylanase presented 167 and 178 U/mL for the best strains (2, 4 and 11) (Fig.…”
Section: Gao Et Al (2008) Isolated a Thermoacidophilicmentioning
confidence: 99%
“…4). However, the aim of this study was the selection of microorganisms and production time (48 h), in other words, in half the time used by Damaso et al (2002). Taragano et al (1997) studied an A. niger strain using wheat bran as substrate and the maximum polygalacturonase (PG) activity obtained was 30 U/mL.…”
Section: Gao Et Al (2008) Isolated a Thermoacidophilicmentioning
confidence: 99%
“…Cost of substrate plays a major role in the economics of enzyme production (15). Hence approach to use cheaper lignocellulosic (corncobs) rather than opting for expensive cellobiose will decrease cost of BGL production.…”
Section: Kinetics Of Enzyme Production Following Growth On Different mentioning
confidence: 99%
“…This work examines the potential of a DG resistant mutant of H. lanuginosa for production of BGL and evaluates the key role of substrate, nitrogen source, pH of the medium and temperature in the life of a thermophilic mould during growth and to maximize the production of BGL as reported in other mutant organisms (12,15,21).…”
Section: Introductionmentioning
confidence: 99%